Analisis Pengembangan Sumber Daya Manusia di BPJS Ketenagakerjaan Cabang Karawang - Alfianti, Laila (SEED: Journal of Scientific Research, 2024)
Human resources are employees who are ready, capable, alert and are very important assets in an organization so that they are able to achieve organizational goals. Employee performance is greatly influenced and even depends on their human resource development capabilities. The aim of this research is to determine the development of human resources at the BPJS Employment Karawang branch office. This research was conducted to conclude and analyze the development of BPJS Employment Karawang branch human resources as an improvement in employee performance. This research was conducted at BPJS Employment with a population of 32 employees and the specified sample was 6 people